Preliminary study on laser texturing of glass: Techniques, process parameters, and initial findings - Rai, Rahool; Mahadzir, Ishak; Aiman, Mohd Halil; Quazi, Moinuddin Mohammed (Elsevier Ltd, 2025)
This paper explores the preliminary study regarding the Laser Texturing on soda-lime glass to modify its functionality to achieve a superhydrophobic surface. Glass, a prominent material in various industries, is particularly crucial in the automotive sector for manufacturing windshields and in renewable energy applications like solar panels. Various laser parameters such as power, scanning speed, and repetition rate were studied for trial to understand their impact on surface morphology and functionality. Initial findings reveal that laser texturing can effectively improve glass surface properties, creating superhydrophobic surfaces while maintaining optimal transparency. However, challenges were encountered in achieving the desired textures without compromising glass integrity. Therefore, the study concludes that trials faced challenges due to the transparent and brittle nature of the glass, resulting in damage from higher temperatures and brittleness, this study provides valuable insights for optimizing laser parameters and exploring alternative substrate preparation methods to advance the development of functional glass surfaces for industrial applications.